A Clinical Study of Cancer Disclosure in Elderly Patients with Oral Cancer - Komori, Takahide; Fujioka, Manabu; Yokoo, Satoshi; Shibuya, Yasuyuki; Umeda, Masahiro; Ishida, Yoshiki; Minamikawa, Tsutomu; Komatsubara, Hideki; Ojima, Yasutaka (Ronen Shika Igaku, 2003)
Radical operation has been more frequently applied to elderly patients with oral cancer, as a rezult of recent development in medical treatment In general, informed consent is important for patients to choose their treatment, but in Japan elderly patients with cancer have not usually been informed of their diagnosis. We studied elderly patients with oral cancer clinically, with special reference to the current trend of informed consent including cancer disclosure. The subjects of this study were 16 patients over 75 with oral cancer who were treated at our hospital between 2000 and 2002. Most of them had rather advanced cancer of stage III-IV. Fourteen of the 16 patients had some associated diseases, such as dimentia, hypertension, heart disease, cerebral infarction, lung disease, kidney disease, and rheumatism. Performance status (PS) was 0-1 in 6 patients, and 2-3 in 10 patients. 50% of the patients older than 75 years were informed of their diagnosis, while the disclosure rate for those younger than 75 years was 90.5%. The reasons for non-disclosure were mental disturbance by dimentia in 2 patients and patient's request in one, while in 5 patients cancer was not disclosed because of their advanced age, advanced stage, family's preference, or the former doctor's policy. Surgery was performed in 10 patients, radiotherapy in 1, and chemotherapy in 1. Four patients did not undergo any therapy because of their highly advanced stage, poor general condition, or of their family's refusal. Seven of 10 patients who underwent surgery survived in good health and recovered to the level of preoperative ADL, although 1 patient died of neck metastasis, 1 of distant metastasis, and 1 was not followed up.